The Dynamics of Arabic Synonyms and Semantic Sensitivity in Foreign Language Learning: A Linguistic-Educational Integration Approach - Assagaf, Muhammad Ridha (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study employs a linguistic-educational approach to analyze the dynamics of Arabic synonyms in the context of foreign language learning. It primarily aims to examine learners’ patterns in using synonyms, identify both linguistic and pedagogical challenges in teaching them, and formulate more effective instructional strategies. Methodology: A descriptive qualitative design with a case study method was applied to students from Madrasah Aliyah Alkhairaat and the Arabic Language Education Program at IAIN Ternate. Data were gathered through classroom observations, in-depth interviews, focus group discussions, and document analysis related to vocabulary learning. Main Findings: The findings reveal that learners tend to use synonyms uniformly, with limited attention to semantic nuance and contextual accuracy. Major challenges include the absence of contextual teaching strategies and learners’ low semantic awareness. Current textbooks and teaching methods remain structural and fail to engage pragmatic dimensions. The study proposes the use of contextual, collocational, and semantic-mapping approaches to improve synonym teaching. Novelty/Originality of this study: This study contributes to the development of more communicative and contextually grounded strategies for teaching Arabic vocabulary, especially in the area of synonym acquisition, by bridging linguistic insights with practical pedagogical applications.